Kinerja Keuangan Sebelum dan Sesudah Penerapan PSAK 72 pada Perusahaan Subsektor Telekomunikasi yang Terdaftar di BEI Periode 2017-2022 - Siregar, Ayu Anjelina (Politeknik Negeri Ambon, 2025)
Introduction: in this study focuses on evaluating how the enforcement of PSAK 72, the Revenue from contracts with customers standard, has shaped the financial results of firms in Indonesia’s telecommunications industry traded on its stock exchange. PSAK 72, effective January 1, 2020, replaced PSAK 23 by introducing a five-step revenue recognition model aimed at improving transparency and comparability, which may affect financial ratios. The research seeks to determine whether the levels of profitability, liquidity, and asset efficiency experienced notable changes between the periods preceding and following the implementation of PSAK 72.Methods: In this quantitative comparative study, secondary data were compiled from publicly released financial reports of 13 telecommunications-related firms spanning 2017 through 2022. In this research, financial performance is evaluated using four key metrics: GPM (Gross Profit Margin), NPM (Net Profit Margin), CR (Current Ratio), and TAT (Total Asset Turnover). Data analysis includes descriptive statistics and normality testing, and applies the Wilcoxon Signed Rank Test to assess differences between the pre-implementation period (2017–2019) and the post-implementation period (2020–2022).Results: GPM (p = 0.944) and NPM (p = 0.12) did not differ significantly, whereas CR (p = 0.013) and TAT (p = 0.021) showed significant changes, indicating that PSAK 72 influences liquidity and asset utilisation but not profitability. The findings suggest that applying PSAK 72 influences certain aspects of financial performance, offering insights that management, investors, and regulators can utilise to understand better the financial reporting implications of the new revenue recognition standard. Keywords: PSAK 72, Financial Performance, Gross Profit Margin, Net Profit Margin, Current Ratio, Total Assets Turnover